Primers application with the Tso31 gene target in the molecular identification of Taenia solium - Habibah, Nur; Bekti, Heri Setiyo; Kumara Dewi, Ni Wayan Rika; Rinawati, Luh Putu; Burhannuddin, Burhannuddin; Rakhmawati, Aprilia (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2021)
Background: taeniasis is a zoonotic disease caused by Taenia spp. Human taeniasis caused by Taenia solium can be acquired after consumption of raw insufficiently cooked infected pork meat. Pigs are intermediate host for T.solium. Pigs acquired this infection by eating human feces that contained T.solium eggs. Pigs infected with T.solium can be transmitted to humans. Purposes: identification of T.solium in pig is important because it is indicator of T.solium transmission. Microscopic examination of T.solium eggs is considered less effective and efficient so that many other methods are developed for T.solium detection such as molecular and immunology. Method: This method used specific primer which can detect the Tso31 gene in T.solium. Tso31 gene is one of the most promising antigens to differentiate T.solium from T.saginata. Pig feces samples were taken by random sampling technique from 7 pig farms in Denpasar. Result: from the 30 samples, we found one sample that which gave a single amplification product of 234 bp. This indicates that the pig farms in Denpasar have been infected with T.solium. Conclusion: it is necessary to do meat inspection properly in the market as well as health education about the dangers and impacts of T.solium infection in the community.